Fungsi Hukum Pembangunan Ekonomi dalam Persaingan Usaha Yang Sehat - Kuntonugroho Adnan (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The necessity of law in upholding the principles of the constitution, particularly in governing various aspects of people’s lives, notably its enforcement and impact on economic advancement, holds significant importance. Economic law emerged in response to the rapid expansion and progress of both domestic and global economies. Across nations, legal frameworks are utilized to regulate and supervise economic and socio-technical activities, ensuring that economic progression does not compromise individuals’ rights and welfare. The introduction of the Business Competition Law was aimed at fostering a competitive market economy, allowing for fair competition between economic entities and society. The primary objective of this legislation is to forestall monopolistic practices and unfair business competition. Through the enforcement of business competition law, the aspiration is to attain economic efficiency, leading to the enhancement of public welfare. Monopolistic activities contribute to economic disparities, adversely impacting societal harmony. For instance, collusion among businesses to dictate prices can harm consumers significantly. Essentially, a select few enterprises can engage in agreements to segment markets, control prices, regulate the quality and quantity of goods and services (through cartels), all geared towards maximizing profits swiftly. Such anti-competitive practices are unjust and disadvantageous to consumers. In the global context, fostering healthy business competition is crucial to preventing detrimental business practices and promoting fair economic competition.